2016
DOI: 10.1002/fsn3.392
|View full text |Cite
|
Sign up to set email alerts
|

Safety of micronized palmitoylethanolamide (microPEA): lack of toxicity and genotoxic potential

Abstract: Palmitoylethanolamide (PEA) is a natural fatty acid amide found in a variety of foods, which was initially identified in egg yolk. MicroPEA of defined particle size (0.5–10 μm) was evaluated for mutagenicity in Salmonella typhimurium, for clastogenicity/aneuploidy in cultured human lymphocytes, and for acute and subchronic rodent toxicity in the rat, following standard OECD test protocols, in accordance with Good Laboratory Practice (GLP). PEA did not induce mutations in the bacterial assay using strains TA153… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 20 publications
6
35
0
Order By: Relevance
“…Preclinical and human studies indicate that PEA, especially when co‐micronized together with antioxidants, such as luteolin and polydatin, and in micronized or ultra‐micronized forms, is a therapeutic tool with high potential for the effective treatment of different pathologies characterized by neurodegeneration, (neuro)inflammation and pain. Likewise, PEA also shows high safety, as recently reported by Nestmann (). While it is intuitive why, for a particularly water insoluble compound such as PEA, any formulation aimed at enhancing its specific surface, such as m‐PEA and um‐PEA, is likely to increase tissue exposure to this compound following oral administration, or why co‐administration of PEA with anti‐oxidants should enhance its efficacy, it must be emphasized that full pharmacokinetic/pharmacodynamic comparisons between normal and m‐PEA or um‐PEA, or between PEA composites and the single components thereof, in the same study, have not been reported yet.…”
Section: Discussionsupporting
confidence: 73%
“…Preclinical and human studies indicate that PEA, especially when co‐micronized together with antioxidants, such as luteolin and polydatin, and in micronized or ultra‐micronized forms, is a therapeutic tool with high potential for the effective treatment of different pathologies characterized by neurodegeneration, (neuro)inflammation and pain. Likewise, PEA also shows high safety, as recently reported by Nestmann (). While it is intuitive why, for a particularly water insoluble compound such as PEA, any formulation aimed at enhancing its specific surface, such as m‐PEA and um‐PEA, is likely to increase tissue exposure to this compound following oral administration, or why co‐administration of PEA with anti‐oxidants should enhance its efficacy, it must be emphasized that full pharmacokinetic/pharmacodynamic comparisons between normal and m‐PEA or um‐PEA, or between PEA composites and the single components thereof, in the same study, have not been reported yet.…”
Section: Discussionsupporting
confidence: 73%
“…These findings are consistent with results of previous studies on the lack of PEAum cytotoxicity and its overall in vivo safety profile. 1,9,52 Our findings suggest that PEA-um effectively downmodulated compound 48/80-induced MC degranulation in the model used. However, some limitations should be considered when interpreting the data.…”
Section: Discussionmentioning
confidence: 62%
“…In the present ex vivo model, exposing skin organ cultures to PEA‐um for 96 h did not elicit any change in either the epidermal or dermal skin compartments, in terms of epidermal thickness or keratinocyte proliferation, the same pattern of keratinocyte differentiation markers, unchanged MC density and degranulation state, compared to vehicle‐treated samples. These findings are consistent with results of previous studies on the lack of PEA‐um cytotoxicity and its overall in vivo safety profile …”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PEA reduces chronic and neuropathic pain associated with numerous pathological conditions and reduces pain and improves function in patients with temporomandibular disorders . Importantly, PEA possesses an optimum tolerability profile, conditions fundamental for chronic treatment of the elderly …”
Section: Potential New Targets For the Treatment Of Degenerative Joinmentioning
confidence: 99%
“…115,116 Importantly, PEA possesses an optimum tolerability profile, conditions fundamental for chronic treatment of the elderly. 86,87,117,118 Both membrane and nuclear receptors appear to be important targets for controlling disease progression. Among membrane receptors, endocannabinoids may be of particular interest, as they play a key role in bone formation, resorption, and growth.…”
Section: Potential New Targets For the Treatment Of Degenerative Joinmentioning
confidence: 99%